Prospective Anti-Aging Benefits of Mackerel Scad Collagen Peptides Through Anti-Hyaluronidase Activity - Herawati, Elisa; Agnesia, Pipin (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
The increased activity of the hyaluronidase enzymes speeds up the degradation of hyaluronic acid in the skin, leading to reduced elasticity and the formation of fine wrinkles, eventually contributing to skin aging. Mackerel scad (Decapterus macarellus) is a promising candidate as a skin anti-aging substance due to its particular amino acid composition. Native collagen and collagen peptides from mackerel scad skin were extracted using pepsine soluble collagen and hydrolysis with collagenase II enzyme. The amino acid profile of collagen was determined using HPLC analysis. An anti-hyaluronidase activity test was done using the spectrophotometry assay to express the content of N-acetyl glucosaminoglycan, and IC50 was calculated. Results showed that mackerel scad collagen contains 17 amino acids, with the highest content of glutamic acid, 8.20%; aspartic acid, 6.70%; glycine, 5.37%; arginine, 4.24%; and proline, 3.84%. The collagen from the extraction results had relatively low anti-hyaluronidase activity (IC50 326.05 ± 6.77 ppm). However, when it was broken down into smaller collagen peptides, the anti-hyaluronidase activity increased to IC50 100.78 ± 0.17 ppm. This indicated that the hydrolysis of collagen into collagen peptides with a smaller molecular weight increased its capacity to inhibit hyaluronidase. These findings suggest that D. macarellus collagen peptides have the potential to inhibit skin aging by inhibiting hyaluronidase enzyme activity.